Risk and protective factors in the mental health of elite sports coaches: A scoping review - Tomasz Kowalski; Natasza Nowosadko; Weronika Mazur; Małgorzata Sławińska; Julia Karbowska; Joanna Zając; Wojciech Waleriańczyk; Joanna Gorgol-Waleriańczyk (International Journal of Sports Science & Coaching, 2026)
Objective Mental health is gaining recognition in sport, but research on coaches remains scarce, and even sparser in elite coaches, despite their central role in high-performance environments. This review examines and synthesises evidence on risk and protective factors related to elite coaches’ mental health. Methods Scoping review following Joanna Briggs Institute and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Systematic searches were conducted in seven databases (Scopus, Embase, MEDLINE Ultimate, PubMed Central, APA PsycINFO, ERIC, SPORTDiscus) on August 20, 2025, without restrictions on publication year. Additional hand-search (snowballing and thematic reviews screening) was conducted between 15 and 30 October 2025. Results We screened 4306 records, and 84 studies investigating 5570 elite coaches were included. Most studies originated from WEIRD (Western, Educated, Industrialized, Rich, and Democratic) countries, employed qualitative or cross-sectional design, and examined mixed or team sport samples. Majority of studies were published in the last decade. Six key thematic areas were identified: job characteristics, social and organisational support, personal resources and individual characteristics, coping styles, work–life interface, and lifestyle. Conclusions While mental health concerns are prevalent among elite coaches, research on risk and protective factors remains sparse, calling for more diverse, longitudinal, and intervention-based studies. Future research should adopt unified terminology, standardized reporting of contextual and participant characteristics, and greater adherence to established reporting guidelines.